"We Distrust the Whole Universe": Long-Distance Communications, Emotions, and the Transformation of the Public Sphere in Chile, 1790–1812. - Bowen, Martín (Hispanic American Historical Review, 2025)
This essay examines the emergence of transparency as a communication ideal among elites in Chile during the crisis of the Spanish Empire. While traditional interpretations highlight newspapers and salons as harbingers of modern communication principles, this article foregrounds the role played by long-distance networks and manuscript correspondence in this process. The royal mail was the first institution in the colony to be subjected to demands for total transparency. This, I argue, was tied to how network participants interacted with the specific emotional, political, and social protocols governing the mail. Beginning in the 1790s, anxiety over misinformation and external threats drove colonists to scrutinize and question imperial control over the mail. As the monarchy collapsed in the early nineteenth century, information manipulation and conflicting communication norms caused mounting emotional distress, eventually leading elites to contest censorship and embrace transparency as a radical norm of political communication.